2005
DOI: 10.1038/sj.onc.1208844
|View full text |Cite
|
Sign up to set email alerts
|

ARK5 is transcriptionally regulated by the Large-MAF family and mediates IGF-1-induced cell invasion in multiple myeloma: ARK5 as a new molecular determinant of malignant multiple myeloma

Abstract: ARK5, AMP-activated protein kinase (AMPK)-related protein kinase mediating Akt signals, is closely involved in tumor progression, and its stage-associated expression was observed in colorectal cancer. In this study, we found ARK5 expression in multiple myeloma cell lines expressing c-MAF and MAFB. In addition, gene expression profiling of 351 clinical specimens revealed ARK5 expression in primary myelomas expressing c-MAF and MAFB, suggesting that ARK5 may be a transcriptional target of the Large-MAF family. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…Aberrant expression of c-Maf activates multiple pathways that mediate tumorigenesis either by the direct induction of cell cycle proteins or indirectly by promoting tumor-stroma interactions (Hurt et al, 2004,Suzuki et al, 2005. While ectopic expression of c-Maf transforms chicken embryonic fibroblasts (Kataoka et al, 1993), overexpression of c-Maf, MafB, or L-Maf in primary embryonic neuroretinal cells does not result in their transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of c-Maf activates multiple pathways that mediate tumorigenesis either by the direct induction of cell cycle proteins or indirectly by promoting tumor-stroma interactions (Hurt et al, 2004,Suzuki et al, 2005. While ectopic expression of c-Maf transforms chicken embryonic fibroblasts (Kataoka et al, 1993), overexpression of c-Maf, MafB, or L-Maf in primary embryonic neuroretinal cells does not result in their transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A human acute T-cell leukemia cell line, Jurkat, ATL cell lines, MT-2, ATL-102 and ED-40515(À), chronic lymphocytic leukemia cell lines, MEC2 and MO1043, Burkitt's lymphoma cell lines, Raji and Daudi and multiple myeloma cell lines, U266, XG7, KM5, ILKM-2 and RPMI-8226 were used in this study as described previously. [20][21][22][23][24] For normal controls, peripheral blood mononuclear cells (PBMCs) were obtained from four independent healthy donors upon informed consent after the approval of Institutional Ethical Committee. All cells were cultured in RPMI-1640 medium, supplemented with 10% fetal bovine serum at 371C in a 5% CO 2 incubator.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, ARK5 was identified as a transcriptional target for the c-Maf in MM. 4 The t(14;16) involving the c-maf oncogene was found in 25% of myeloma cell lines 2 but only 2-6% of primary MM samples. 5,6 Patients harboring t(14;16) appear to have a worse outcome.…”
mentioning
confidence: 99%
“…1 Activating kinase domain point mutations in KIT at codon 816 in exon 17, predominantly Asp816Val and less commonly Asp816Phe, are highly associated with mast cell disorders (MCD) and result in ligand-independent kinase signaling. 2,3 A number of studies have shown that KIT mutations can be present in a variety of cell lineages 4 and this results in a spectrum of systemic MCD with associated hematological clonal non-mast cell lineage disease (AHNMCD) that have differing clinical behavior. 5,6 Mast cells in bone marrow (BM) in MCD can be easily enumerated by direct microscopic examination, with the aid of mast cell tryptase or CD117 immunostaining, or by flow cytometric analysis (e.g.…”
mentioning
confidence: 99%